The influence of Alexander von Humboldt’s work in the school geography discipline of High School (Research, Society and Development, 2021)
Although several ceossiste covered in the geography of Basic Education have been pioneered by Alexander von Humboldt, his name and image could be more present at this level of education. This work presents the results of a research that aimed to identify aspects of Humboldt’s work that became relevant to geographic Science and to understand how it is possible to associate / transpose academic geography with school geography. The research, of the documentar type, analyzed the work “The invention of nature – the life and discoveries of Alexander von Humboldt”, read and discussed in remote meetings. From the analyzes, Humboldt’s main discoveries were listed based on four thematic axes: environment, society and culture, politics and curiosities. As examples, we can point to the definition of isotherms, the discovery of the magnetic equator, studies on the dynamics of mineral formation, the direct relationship between human action, through deforestation, and climate change, in addition to acting in other areas, in the social and political spheres. In view of Humboldt’s achievements, we sought to relate these discoveries to the contents covered in the CEFET-MG’s Geography in High School program. Thus, it was possible to point out possibilities for inserting Humboldt, and his studies, into the school geography of Basic Education.